Empty sella Syndrome as a Cause of Hypopituitarism Case study - Yousif Baha'addin Ahmed (Diyala Journal of Medicine, 2018)
Background:Empty sella syndrome is the radiological appearance of an enlarged or deformed sella turcica which is partially or completely filled with cerebrospinal fluid .In 20-50% of patients there may be endocrinologic dysfunction, pan hypopituitarism is present  in 25% of cases and isolated one in 10%.